HUBUNGAN LETAK JANIN DENGAN KEJADIAN KETUBAN PECAH SEBELUM WAKTUNYA PADA IBU BERSALIN - Arif, Ahmad; Kurnia, Eva; Julisa A, Meike (JOURNAL OF HEALTH SCIENCE, 2021)
One of the causes of maternal death is complications, including premature rupture of the membranes which is the rupture of the membranes before delivery. This research is a quantitative research with an analytical survey with a cross sectional approach. The population in this study were all maternity mothers who had been treated at the Kindergarten Hospital. II dr. AK Gani Palembang recorded medical records amounting to 1634 people. The sample of this research used systematic random sampling method. The sample of this study amounted to 94 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of the bivariate analysis found that there was a relationship between fetal position abnormalities (p value = 0.003) and the incidence of premature rupture of membranes in mothers giving birth at the Kindergarten Hospital. II dr. AK Gani Palembang. The advice given to the hospital is expected to be specifically for midwives to be able to provide counseling in the form of providing information and counseling to mothers on the sidelines of their service hours regarding the occurrence of premature rupture of membranes. Keywords : premature rupture of membranes, fetal position abnormalities